Intracellular delivery of fluorescent protein into viable wheat microspores using cationic peptides - Bilichak, Andriy; Luu, Justin; Eudes, Francois (Frontiers in Plant Science, 2015)
Microspores are specialized generative cells with haploid genome that demonstrate the amenability toward embryogenesis under certain conditions. The induced microspore culture technique is largely exploited by the breeding programs of wheat and other crops due to its high efficiency for generation of the large number of haploid plants in the relatively short period of time. The ability to produce mature double haploid plant from a single cell has also attracted attention of the plant biotechnologists in the past few years. More importantly, the possibility to deliver proteins for improvement of embryogenesis and the genome modification purposes holds great potential for transgene-free wheat biotechnology. In the present study, we examined the ability of cationic and amphipathic cell penetrating peptides (CPPs) to convey a covalently-linked mCherry protein inside the viable microspores. We demonstrate that the affinity of CPPs to the microspore cells dependents on their charge with the highest efficiency of CPP-mCherry binding to the cells achieved by cationic CPPs (penetratin and R9). Additionally, due to overall negative charge of the microspore cell wall, the successful uptake of the protein cargo by live microspore cells is attained by utilization of a reversible disulfide bond between the R9 CPP and mCherry protein. Overall, the approach proposed herein can be applied by the other biotechnology groups for the fast and efficient screening of the different CPP candidates for their ability to deliver proteins inside the viable plant cells.